Proteomics as a tool to decipher plant responses in arbuscular mycorrhizal interactions: a meta‐analysis. Issue 6 (3rd January 2023) - Domingo, Guido; Vannini, Candida; Bracale, Marcella; Bonfante, Paola
Abstract: The beneficial symbiosis between plants and arbuscular mycorrhizal (AM) fungi leads to a deep reprogramming of plant metabolism, involving the regulation of several molecular mechanisms, many of which are poorly characterized. In this regard, proteomics is a powerful tool to explore changes related to plant–microbe interactions. This study provides a comprehensive proteomic meta‐analysis conducted on AM‐modulated proteins at local (roots) and systemic (shoots/leaves) level. The analysis was implemented by an in‐depth study of root membrane‐associated proteins and by a comparison with a transcriptome meta‐analysis. A total of 4262 differentially abundant proteins were retrieved and, to identify the most relevant AM‐regulated processes, a range of bioinformatic studies were conducted, including functional enrichment and protein‐protein interaction network analysis. In addition to several protein transporters which are present in higher amounts in AM plants, and which are expected due to the well‐known enhancement of AM‐induced mineral uptake, our analysis revealed some novel traits. We detected a massive systemic reprogramming of translation with a central role played by the ribosomal translational apparatus. On one hand, these new protein‐synthesis efforts well support the root cellular re‐organization required by the fungal penetration, and on the other they have a systemic impact on primary metabolism.